The order of global and local information processing in visual stimuli - Martišius, V. (Psichologija, 1989)
In the present report basing on the works of contemporary authors a conclusion is made that it is the global aspects of images that are maįnly available for the initial processing. When local and global dimensions are discriminably equal in some cases only global precedence is obtained at the small exposure duration. At the longer exposure duration both local and global interferences are demonstrated. Stritly discrete - models are not able to explain all experimental data. The processing of -local and global information is simultaneously completed at several processing levels.
Keywords: information processing; visual stimuli